Pengaruh Desain Produk Dan Kualitas Produk Terhadap Keputusan Pembelian : Survei Pada Konsumen Mutiara Tikar Di Tasikmalaya - Maulana Tegar Arafi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the simultaneous and partial effect of product design and product quality on carpet purchasing decisions at Mutiara Tikar Tasikmalaya. The method used in this study is a survey method with a quantitative approach. The population studied was 100 respondents. The data collected is in the form of primary data and secondary data. Data analysis in this study used multiple linear regression analysis using SPSS version 24 software. The results showed that product design and product quality simultaneously had a significant effect on the purchasing decision of products Mutiara tikar in Tasikmalaya Product Design, partially had a significant effect on product purchasing decisions Mutiara Tikar in Tasikmalaya. Product quality partially has a significant effect on the purchasing decision of Mutiara Tikar carpet products in Tasikmalaya.